Stress and food intake among university students - is there a relationship? - Cheng, Shi-Hui; Muhammad Khair Mohd Kamil, (Penerbit Universiti Kebangsaan Malaysia, 2020)
There is a growing interest in the effects of stress on food consumption. Studies suggest that stress could either increases or decreases food consumption among university students. As the prevalence of stress is evident among university students in various countries, this study aims to investigate the relationship of stress on dietary consumption among undergraduate students of a private university. A cross-sectional study was carried out and a total of 100 participants aged between 18-25 years and non-smokers were recruited. Anthropometric data was measured and participants were asked to answer a questionnaire which accessed their sociodemographic background, stress level, frequency of food intake and 3-day dietary intake. The data collected were then analysed using SPSS software. This study found that males consumed cooked vegetables less frequently than females (male= 2.38±1.48; female= 3.68±1.31, p<0.001) while consumed soft drinks more frequently than females (male= 1.90±1.31; female= 1.28 ±1.24, p<0.05). In addition, stressed group consume significantly lower energy, fat (including saturated fat, monounsaturated fatty acids and polyunsaturated fatty acids) and calcium than non-stressed group (p<0.05). In conclusion, the prevalence of stress among university students in this study was 40%. Students eat lesser when they are in stress and this could negatively impact their health. Therefore, stress management interventions need to be implemented to help the university students to manage their stress and this could help to promote healthy eating behaviour among university students.